Combined temporal arteriography and selective biopsy in suspected giant cell arteritis. Issue 2 (April 1980) - Sewell, J R; Allison, D J; Tarin, D; Hughes, G R
Abstract : Superficial temporal arteriography was studied by selective biopsy of abnormal arterial segments and random biopsy of the main stem in 33 patients with clinically supected giant cell arteritis. Of the total of 33 temporal arteriograms 9 showed definite abnormalities (7 in the periphery and 2 in the main stem). Selective biopsy of the 7 peripheral abnormal segments showed arteritis in only 2, narrowing of the vessels in the remainder being due to atheroma (3) and fibrointimal thickening (2)--that is, 5 'false positives' for temporal arteritis on arteriography. Histological evidence of arteritis was found in 9 patients, only 5 of whom had clearly abnormal arteriograms--that is, 4 'false negatives'. Thus temporal arteriography appears to have low sensitivity for identifying arteritic lesions and also frequently gives 'false positive' results. It is concluded that temporal arteriography is not a satisfactory alternative to biopsy, and that its value as an adjunct to selective biopsy is limited because of its frequent failure to detect lesions found histologically.